ACTIVE AND INTERACTIVE FORMS OF ORGANIZING ACTIVITIES IN HISTORY LESSONS (Conferencea, 2022)
The article considers active and interactive forms of conducting history classes as the most effective in the implementation of urgent educational tasks, involving the direct participation of students in the formation of the necessary knowledge, skills and abilities.